PURIFIKASI BIOGAS MENGGUNAKAN PELET SEKAM PADI TERAKTIVASI UNTUK MENINGKATKAN KONSENTRASI CH4 DALAM BIOGAS - Rosiana Indrawati; Joko Susilo (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2018)
The availability of fossil fuels as the main supplier of national energy is increasingly expensive and limited. Biogas appears as an alternative energy source. The purity of CH4 produced by biogas becomes very important, because it affects the calorific value produced. This study aims to determine the effect of biogas purification using rice husk pellet adsorbent on CH4 content in biogas. The independent variable is the height of the adsorbent 5 cm, 10 cm and 15 cm. Contact time is 30 minutes, 60 minutes and 90 minutes. While the controlled variables include activation of adsorbents with heating temperatures of 1200C. The dependent variable observed was the percentage of CH4 content before and after purification. Sampling was carried out on day 20. Based on the gas chromatography test results showed that the largest CH4 gas content was found in SPWT90TA5 purification reactor, rice husk adsorbent namely 5 cm adsorbent height variation and 90 minutes residence time which was 32,393 with a percentage of CH4 content increase of 260.3% from the initial content of CH4 gas before the purification process which was 8.99. And the lowest CH4 gas content is in the SPWT60TA 10 sample which is 6.252 or reduced by 30% from the initial CH4 content before purification is carried out. The conclusion is that biogas purification using rice husk pellet adsorbent can adsorb impurities in biogas and increase methane levels in biogas.